PENDIDIKAN FULL DAY SCHOOL DALAM PERSPEKTIF EPISTEMOLOGI MUHAMMAD ‘ABID AL- JABIRI - Hasan Baharun; Saudatul Alawiyah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
This paper presents about full day school education in the epistemology perspective of Muhammad 'Abid Al-Jabiri. Muhammad 'Abid Al-Jabiri is one of contemporary Islamic thinkers with the theories of bayani, ‘irfani and burhani. Where the theory of epistemology serve is a science that comes from a sacred text and the theory of ‘irfani epistemology derived from intuition while the theory of burhani epistemology derived from the principles of logic, ratio and reason. And this paper examines the education of full day school with the theories of bayani, ‘irfani and burhani. With the hope of third theory can be understood as effort to build and create paradigm of society about policy of full day school, so from various problematic causing the pros and cons to full day school concept which have been published by Mendikbud can be overcome.